Nine-year follow up after hematopoietic stem cell transplantation in five multiple sclerosis patients - Elizabeth R. Comini-Frota; Bruna C. C. Marques; Caio Torres; Karoline M. S. Cohen; Eduardo Carvalho Miranda (Arquivos de Neuro-Psiquiatria)
ABSTRACT Multiple sclerosis (MS) is an immune-mediated disease of the central nervous system. Its treatment has focused on inflammation control as early as possible to avoid disability. Autologous hematopoietic stem cell transplantation (AHSCT) has been used for treating MS since 1996, with recent decisive results regarding benefits in long-term efficacy. Five patients followed up at an MS center in Belo Horizonte, Brazil, who had relapsing-remitting MS with high disease activity, underwent AHSCT between 2009 and 2011. They were evaluated clinically, with magnetic resonance imaging, and by the EDSS every six months after transplantation, up to July 2018. The patients were four women and one man, with ages ranging from 25-50 years, and time since disease onset ranging from 4-17 years at the time of the procedure. Four patients improved, one patient was stabilized, and all patients were free of disease activity after 5-9 years. Through improving patient selection and decreasing the time from disease onset, AHSCT could stop epitope spreading and disease progression. Despite multiple other therapeutic choices being approved for relapsing-remitting MS, AHSCT continues to be a treatment to consider for aggressive MS disease.